Improvement of Transplanting Rice Yield and Nitrogen Use Efficiency by Increasing Planting Density in Northeast China Under the Optimal Nitrogen Split-Fertilizer Applications - Zichen Liu; Wanchun Li; Shujuan Geng; Rui Zhang; Man Dou; Meikang Wu; Liangdong Li; Dongchao Wang; Xiaoshuang Wei; Ping Tian; Meiying Yang; Zhihai Wu; et al. (Agriculture)
There are few studies on how nitrogen (N) fertilizer application rates and transplanting densities impact rice yield, root distribution, and N use efficiency in the cold regions of Northeast China. This research involved a two-year field trial utilizing Jinongda 667 as the material. In 2021, three N split-fertilizer applications—T1 (6:3:1), T2 (5:3:2), T3 (4:3:3)—and two transplanting densities—D1 (30 cm × 13.3 cm) and D2 (30 cm × 20 cm)—were compared with the conventional cultivation mode (T0: 175 kg N hm−2, 6:3:1), whereby the N application mode most suitable for increasing density was explored. In 2022, four N application levels—0 (N0), 125 (N1), 150 (N2), and 175 (N3) kg N hm−2—were assessed under the same density treatment to analyze the yield, resource utilization efficiency, and root traits of Jinongda 667. The results indicated that when the transplanting density was 30 cm × 13.3 cm, the application of 5:3:2 fertilizer was more conducive to improving rice yield. Increasing planting density under reduced N input significantly enhanced both rice yield and N use efficiency. In contrast to the conventional cultivation method (D2N3), the treatment of increased planting density (D1N2) under reduced N input led to a 21.2% rise in the number of panicles per square meter and an 8.6% boost in rice yield. Furthermore, increasing planting density under reduced N input significantly enhanced the agronomic efficiency of N fertilizer, the apparent utilization rate, and the N harvest index. It also boosted the SPAD value, photosynthetic rate, and the utilization efficiency of light and N resources in rice. However, it was noted that root enzyme activity decreased. This study demonstrated that increasing planting density, combined with the N application mode of 5:3:2 and an N application rate of 150 kg hm−2, maximized resource utilization efficiency, optimized root absorption capacity, and resulted in higher yields.